Fast determination of citreoviridin residues in rice using a monoclonal antibody-based immunochromatographic strip assay - Yue Li; Guohao Jin; Liqiang Liu; Jing Xiao; Hua Kuang (Food and Agricultural Immunology, 2020)
Citreoviridin (CTV) is a toxic secondary metabolite that can be found in mouldy cereals. In this study, a sensitive and ethanol-tolerant anti-CTV monoclonal antibody (6B2) was produced with a 50% inhibition concentration of 4.1 ng/mL and then labelled using gold nanoparticle (GNP). Based on competitive inhibition of the binding of CTV-COOH-BSA conjugate sprayed onto a membrane to limited GNP-labelled antibody by free CTV in the samples, an easy-to-operate immunochromatographic strip (ICS) was developed for the fast screening of CTV in rice. The results are seen as a colour change within 5-10 min. We used relatively safe ethanol instead of highly toxic methanol or chloroform as the extraction solution and found a visible detection limit of 100 μg/kg and cut-off value of 1000 μg/kg. The developed ICS assay worked well and represented a reliable, safe, fast and a highthroughput method for the detection of CTV residues in rice samples.